Auditoría de control interno a inventario de productos de la empresa agro Manobanda hermanos S.A. agromaban, canton Quevedo, año 2012. - Cedeño Vera, Bexy Isabel (2014)
The application of this work is the implementation of an audit of internal control of the inventory account of a company dedicated to the export of cocoa, specifically AGRO MANOBANDA HERMANOS S.A AGROMABAN located at KM 1 WAY VALENCIA, the respective auditing implemented in the period 2012, the purpose of the audit is to verify the reasonableness of the inventory account in the financial statements, the study supports the tools used regarding the analysis financial as: assessment of financial indicators, the analysis system using systematic and priority of the inventory item……